Analysis on visual design principles of a webpage - Bulli Babu, R; Akhil Reddy, A; Praveen Kumar, G (International Journal of Engineering and Technology, 2018)
Web page means a document which is to be shown on a browser and its design must be internet user based. The crucial aspect of a webpage design fabricated represents the content in webpage and it must be understood by user very effectively This paper/tabloid/thesis particularises/specifies on a decent visual style will build the interactive programs understood and be employed by a lot of precisely, the analytics is that the measuring, assortment and analysis of web page information. Page statistics and user metrics square measure the necessary consider most of the online analytics tool. To convey the certain information, we must design exact emotions regarding what the web page is of about. A unique and individualised emotional/expressive style of a website will impress web users deeply, initiate web users to click/tick sharply/promptly.
Keywords: Bootstrap; FTP Hosting; Responsive Webpage; WYSIWYG